Japan, the sustainable society : the artisanal ethos, ordinary virtues, and everyday life in the age of limits - Lie, John (University of California Press, 2022)
"By the late twentieth century, Japan had gained worldwide attention as an economic powerhouse. Having miraculously risen from the ashes of World War II, it was seen by many as a country to be admired if not emulated. But by the early 1990s, that bubble burst in spectacular fashion. The Japanese economic miracle was over. In this book, John Lie argues that in many ways the Japan of today has the potential to be even more significant than it was four decades ago. As countries face the prospect of a world with decreasing economic growth and increasing environmental dangers, Japan offers a unique glimpse into what a viable future might look like-one in which people acknowledge the limits of the economy and environment while championing meaningful and sustainable ways of working and living. Beneath and beyond the rhetoric of growth, some Japanese are leading sustainable lives and creating a sustainable society. Though he does not prescribe a one-size-fits-all cure for the world, Lie makes the compelling case that contemporary Japanese society offers a possibility for how other nations might begin to valorize everyday life and cultivate ordinary virtues"--